Airchemistry at Neumayer station, Antarctica during the year 2024 - Jurányi, Zsófia; Bösch, Tim (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2025)
The main task of the Neumayer Aerosol and Trace Gas (former Air Chemistry) Observatory at Neumayer III Station is to provide continuous, year-round as well as long-term data records for important gaseous and particulate trace components of the troposphere. The data set reports on long term atmospheric observations (aerosol scattering and back scattering coefficient, surface ozone, and aerosol particle number concentration) at the Air Chemistry Observatory (Neumayer III, Antarctica) between 1 January 2024 and 31 December 2024, measured about 5-7 m above ground with 60 sec resolution. For additional information about the observatory visit homepage: https://www.awi.de/en/science/long-term-observations/atmosphere/antarctic-neumayer/air-chemistry.html
Keywords: aerosol; Antarctica; Spuso; surface ozone